2013
DOI: 10.4162/nrp.2013.7.4.281
|View full text |Cite
|
Sign up to set email alerts
|

Effects of parental folate deficiency on the folate content, global DNA methylation, and expressions of FRα, IGF-2 and IGF-1R in the postnatal rat liver

Abstract: We examined the effect of parental folate deficiency on the folate content, global DNA methylation, folate receptor-alpha (FRα), insulin-like-growth factor-2 (IGF-2) and -1 receptor (IGF-1R) in the liver and plasma homocysteine in the postnatal rat. Male and female rats were randomly fed a folic acid-deficient (paternal folate-deficient, PD and maternal folate-deficient, MD), or folic acid-supplemented diet (paternal folate-supplemented, PS and maternal-folate-supplemented, MS) for four weeks. They were mated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 34 publications
2
31
0
1
Order By: Relevance
“…On the contrary, Henderson, Aleliunas, Tai, Green, and Devlin () found that serum IGF‐1 concentrations were decreased in the offspring born to VB 12 ‐deficiency dams, whereas maternal dietary VB 12 supplementation returned the offspring serum IGF‐1 to normal. Similar, the expressions of hepatic IGF‐1 mRNA and protein were increased in the MD compared with CON offspring, further indicated that maternal MD supplement induced greater hepatic IGF‐1 expression and resulted in elevated circulating IGF‐1, which agrees with the results in rat that serum IGF‐1 concentrations and hepatic IGF‐1 mRNA abundance were upregulated in the offspring born to folate‐sufficiency dams (Mejos, Kim, Lim, & Chang, ). Therefore, the increases of hepatic IGF‐1 expression and serum IGF‐1 were the contributing factor to improve the growth performance of offspring with maternal MD supplementation.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…On the contrary, Henderson, Aleliunas, Tai, Green, and Devlin () found that serum IGF‐1 concentrations were decreased in the offspring born to VB 12 ‐deficiency dams, whereas maternal dietary VB 12 supplementation returned the offspring serum IGF‐1 to normal. Similar, the expressions of hepatic IGF‐1 mRNA and protein were increased in the MD compared with CON offspring, further indicated that maternal MD supplement induced greater hepatic IGF‐1 expression and resulted in elevated circulating IGF‐1, which agrees with the results in rat that serum IGF‐1 concentrations and hepatic IGF‐1 mRNA abundance were upregulated in the offspring born to folate‐sufficiency dams (Mejos, Kim, Lim, & Chang, ). Therefore, the increases of hepatic IGF‐1 expression and serum IGF‐1 were the contributing factor to improve the growth performance of offspring with maternal MD supplementation.…”
Section: Discussionsupporting
confidence: 84%
“…The age of the offspring reaches to 110 kg: CON = 196.2 days; MD = 192.2 days. *p < 0.05, significantly different from CON (Mejos, Kim, Lim, & Chang, 2013). Therefore, the increases of hepatic IGF-1 expression and serum IGF-1 were the contributing factor to improve the growth performance of offspring with maternal MD supplementation.…”
Section: Discussionmentioning
confidence: 79%
“…Additionally, folate deficiency has been associated with global DNA hypomethylation [11]. DNA methylation is critical in the regulation of gene expression and in the maintenance of genome stability.…”
Section: Nucleusmentioning
confidence: 99%
“…Impaired nucleotide synthesis can also cause increased mutation rates, as well as genome instability, including DNA double strand breaks and chromosome damage. Additionally, folate deficiency has been associated with aberrant DNA methylation because methionine is used to synthesize AdoMet, the major cellular methyl donor [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation